GATA3, HDAC6, and BCL6 Regulate FOXP3+ Treg Plasticity and Determine Treg Conversion into Either Novel Antigen-Presenting Cell-Like Treg or Th1-Treg - Xu, Keman; Yang, William Y.; Nanayakkara, Gayani Kanchana; Shao, Ying; Yang, Fan; Hu, Wenhui; Choi, Eric T.; Wang, Hong; Yang, Xiaofeng (Frontiers in Immunology, 2018)
We conducted an experimental database analysis to determine the expression of 61 CD4+ Th subset regulators in human and murine tissues, cells, and in T-regulatory cells (Treg) in physiological and pathological conditions. We made the following significant findings: 1) adipose tissues of diabetic patients with insulin resistance upregulated various Th effector subset regulators; 2) in skin biopsy from patients with psoriasis, and in blood cells from patients with lupus, effector Th subset regulators were more upregulated than downregulated; 3) in Rosiglitazone induced failing hearts in ApoE deficient (KO) mice, various Th subset regulators were upregulated rather than downregulated; 4) aortic endothelial cells activated by pro-atherogenic stimuli secrete several Th subset promoting cytokines; 5) in Treg from follicular Th (Tfh)-transcription factor (TF) Bcl6 KO mice, various Th subset regulators were upregulated; whereas in Treg from Th2-TF GATA3 KO mice and HDAC6 KO mice, various Th subset regulators were downregulated, suggesting that Bcl6 inhibits, GATA3 and HDAC6 promote, Treg plasticity; and 6) GATA3 KO-, and Bcl6 KO-Treg upregulated MHC II molecules and T cell co-stimulation receptors, suggesting that GATA3 and BCL6 inhibit Treg from becoming novel APC-Treg. Our data implies that while HDAC6 and Bcl6 are important regulators of Tregplasticity, GATA3 determine the fate of plastic Tregby controlling whether it will convert in to either Th1-Tregor APC-T-reg. Our results have provided novel insights on Treg plasticity into APC-Treg and Th1-Treg, and new therapeutic targets in metabolic diseases, autoimmune diseases, and inflammatory disorders.